Microfinance Institution (MFIs) and Survival of Micro and Small Enterprises (MSEs): Empirical Evidence of TraderMoni Scheme Beneficiaries in South-Western Nigeria. - Adamolekun, Wole; Obadeyi, J. A; Ogbeide, Sunday Oseiweh; Akande, A. A. (Advances in Social Sciences Research Journal, 2021)
Deregulation in Microfinance Institution (MFIs) in accordance with regulatory policy architecture since 2005 has not fully stimulated sustainability towards the informal system due to the inability of MFIs to access funds and government to judiciously administer credits to beneficiaries of various schemes; this has led to the partial collapse of some schemes in Nigeria; despite Government good intentions of creating employment and alleviating poverty. In view of this, this study assessed Microfinance Institution (MFIs) and Survival of Micro and Small Enterprises (MSEs): Empirical evidence of tradermoni scheme beneficiaries in South-Western Nigeria. The study adopted Tedeschi model (2006) that examined incentives available for borrowers to repay loans. Furthermore, reference was made to Markov Chain model to investigate the response of individual borrower as an applicant and beneficiary of tradermoni scheme in the context of this study. Eighteen MFIs were sampled from 2009 – 2020. Panel data was adopted for the study. The result showed mixed influences of MFIs on survival of MSEs. We are hopeful that findings of this paper would help to fill the existing gap on the influence of MFIs on the survival of MSEs.